2022
DOI: 10.3389/fpsyg.2022.960373
|View full text |Cite
|
Sign up to set email alerts
|

Information needs and development of a question prompt sheet for upper extremity vascularized composite allotransplantation: A mixed methods study

Abstract: BackgroundPeople with upper extremity (UE) amputations report receiving insufficient information about treatment options. Furthermore, patients commonly report not knowing what questions to ask providers. A question prompt sheet (QPS), or list of questions, can support patient-centered care by empowering patients to ask questions important to them, promoting patient-provider communication, and increasing patient knowledge. This study assessed information needs among people with UE amputations about UE vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The Myths and Facts section provides users with an opportunity to both apply their knowledge of VCA as a treatment option and receive feedback as they separate myths from facts ( Figure 3 ). The Resources section provides a question prompt sheet, which is a structured list of questions about UE VCA that can be used by patients when communicating with their physicians [ 38 ]. The structured list of questions enhances users’ retention of information about UE VCA and transfers concepts to real-world applications with physician-patient conversations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Myths and Facts section provides users with an opportunity to both apply their knowledge of VCA as a treatment option and receive feedback as they separate myths from facts ( Figure 3 ). The Resources section provides a question prompt sheet, which is a structured list of questions about UE VCA that can be used by patients when communicating with their physicians [ 38 ]. The structured list of questions enhances users’ retention of information about UE VCA and transfers concepts to real-world applications with physician-patient conversations.…”
Section: Resultsmentioning
confidence: 99%
“…The selection of medical content for the website was guided by elements of informed consent, including the risks, benefits, procedures, alternatives, and voluntary nature of UE VCA. In addition, content was driven by a review of the literature; conversations with health care providers working in UE VCA (eg, UE VCA clinicians or surgeons, hand reconstructive surgeons, and occupational therapists); in-depth and semistructured interviews with individuals with UE loss and UE VCA candidates, participants, and recipients about their information needs regarding UE VCA [ 38 ]; and focus groups, which provided input on the website sitemap and topic and subtopic headers. Participants suggested topics that should be included or removed.…”
Section: Methodsmentioning
confidence: 99%
“…31 Patients also reported identity concerns of transforming into "Frankenstein" 52 through VCA, as found elsewhere. 53 Other study participants desired further information before deciding, 17 including about costs and insurance coverage, as documented elsewhere. 30 Consistent with previous research, a key finding was limited knowledge about UE VCA among individuals with UE amputations.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a focus group study found that members of the public had little knowledge of VCA; reported information needs about who could donate, who needs a VCA, and the success rate; and maintained misunderstandings of VCA ( Ferzola et al, 2022 ). A research study conducting interviews and focus groups among individuals with upper extremity amputations and individuals pursuing or had received an upper extremity VCA about decision-making to pursue VCA found that participants desired extensive information about upper extremity VCA in order to make decisions ( Gacki-Smith et al, 2022 ). Many reported that their decisions in favor of pursuing upper extremity VCA were based on the prospect of regaining functionality and its associated independence, increasing social and physical confidence, and enabling more active parental involvement in childrearing; by contrast, those against pursuing upper extremity VCA reported concerns about their health or limb functioning becoming “worse off,” the rigorous rehabilitation process, and having adapted to life without upper limb(s) ( Gordon, 2022 ).…”
Section: Informed Consent and Potential Graft Loss (‘Exit-strategies’...mentioning
confidence: 99%